KADIS S3 SEGER (Membudayakan Disiplin dan Sopan Santun Dengan Sehat dan Gembira) - Rejo Rejo (Citra Dharma Cindekia, 2023)
Since August 2021, SMPN 3 Mojokerto initiated limited face-to-face learning, which subsequently evolved into full-fledged in-person education by January 2022, implementing health protocols in response to the COVID-19 pandemic. However, the pandemic's impact became evident in the declining character of students, notably in their discipline and courtesy. To address this issue, the school introduced an initiative known as